2011
DOI: 10.1001/archdermatol.2011.84
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatment of Hypertensive Leg Ulcers With Platelet-Derived Growth Factor-BB

Abstract: Setting: Ambulatory or hospitalized patients from 17 dermatology departments. Patients: Among 64 consecutive randomized patients with 1 or more hypertensive leg ulcers who fulfilled all inclusion criteria, 59 received the allocated intervention, and findings were analyzed. Intervention: Becaplermin gel (human recombinant platelet-derived growth factor-BB, 0.1%, in hydrogel) or hydrogel dressing was applied, both in doses of 1 cm/ cm 2 , once daily for 8 weeks. Follow-up continued for 4 weeks beyond the final g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 20 publications
1
14
0
2
Order By: Relevance
“…For example, exogenous delivery of growth factors by topical application has been explored. However, these approaches have generally found to be ineffective [911] as the soluble growth factors delivered to the wound in these approaches were either proteolysed [12], sequestered by secreted macromolecules (e.g. fibrinogen, α-2-macroglobulin) [13], or removed by exudate before reaching the wound bed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, exogenous delivery of growth factors by topical application has been explored. However, these approaches have generally found to be ineffective [911] as the soluble growth factors delivered to the wound in these approaches were either proteolysed [12], sequestered by secreted macromolecules (e.g. fibrinogen, α-2-macroglobulin) [13], or removed by exudate before reaching the wound bed.…”
Section: Introductionmentioning
confidence: 99%
“…23 Phase II clinical trials showed a potential therapeutic benefit in treating pressure ulcers 24 ; however, this benefit did not persist in subsequent phase III studies. 25,26 In addition, a black box warning was placed on the drug after a postmarketing retrospective cohort study that found an increased rate of mortality secondary to malignancy in certain patients. 25 Although this drug may be useful in treating diabetic neuropathic wounds, its further clinical utility is limited by its potential for dangerous side effects, as well as by a lack of significant efficacy in alternate wound settings.…”
Section: Biological Therapiesmentioning
confidence: 99%
“…Ischemic hypertensive leg ulcers (HLU) are superficial, rapidly spreading necrotic ulcers, occurring in longstanding hypertensive and/or diabetic patients over 60 years of age [1][2][3][4][5]. Arterial hypertension and diabetes have been reported in 95 and 40% of HLU patients, respectively [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Arterial hypertension and diabetes have been reported in 95 and 40% of HLU patients, respectively [3][4][5]. Most authors consider that the clinical presentation of HLU is characteristic, but it remains under-recognized, with a mean delay in diagnosis of 12 weeks [6].…”
Section: Introductionmentioning
confidence: 99%